ANALISIS STRATEGI MARKETING PUBLIC RELATIONS PADA KAMPANYE PERILISAN GLASSTICK MELALUI INSTAGRAM MADFORMAKEUP - Tsabitha Putri Aldri; Arvin Hardian (Jurnal Cakrawala Ilmiah, 2025)
The increasing competition in the local cosmetics industry requires each brand to implement an effective communication strategy, one of which is through Marketing Public Relations (MPR). This study aims to analyze the MPR strategy implemented by Mad for Makeup in the launch campaign of the Glassstick product through Instagram. This research uses a descriptive qualitative method with data collection techniques including interviews, observation, documentation, and literature study. The primary informants were the Marketing Public Relations team and content creators involved in the campaign. This study is analyzed using the Three Way Strategy concept by Thomas L. Harris, consisting of Pull Strategy, Push Strategy, and Pass Strategy. The results show that Mad for Makeup successfully built a positive product image through emotional social campaign content (Pull), delivered product information with strong narratives and appealing visuals (Push), and involved communities and influencers to expand message reach (Pass). This combination of strategies strengthened audience engagement, increased brand awareness, and positioned Mad for Makeup as a progressive and inclusive local brand. This research is expected to serve as a reference for the development of social media-based marketing communication strategies, both theoretically and practically.